PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK (PjBL) TERHADAP HASIL BELAJAR PESERTA DIDIK DI SMA NEGERI 1 AIRMADIDI - Jeilen Gabriella Nikita Nusa; Lenda Lumentah; Marcellino Christofel Mambu (LPPM Politeknik Saint Paul Sorong, 2022)
This study aims to determine the effect of the application of project-based learning (PjBL) on learning outcomes in the physics subject of temperature and heat for students at SMA Negeri 1 Airmadidi. This study used a quasi-experimental design with a Nonequivalent (Pretest-Posttest) Control Group Design. The criteria for the research sample were based on the considerations of researchers and teachers at school, namely class XI MIPA 4 and 5. The research data was collected using an instrument to test the ability to understand temperature and heat material. The results showed that there was an increase in the learning outcomes of students using the project-based learning model (PjBL), namely 85.85%, compared to conventional learning models which only obtained 78.75%.